Pengembangan Kurikulum Mandiri Berbasis Capaian di SMA Al Hikmah Boarding School Batu - Muhammad Fahmi Hidayatullah; Ahmad Sodikin; Anwar Sa’dullah; Imam Bukhori (TADRIS: Jurnal Pendidikan Islam, 2021)
Reforms and decentralization helped to accelerate progress towards achieving progress. Educational autonomy needs to be maximized in balancing the currents of the global climate. The ability of educational institutions to adapt to the global climate is very much needed. So that when faced with the current Covid-19 outbreak, schools can survive and run stably. The key component in the management of education is the curriculum. The role of the curriculum as the brain of the operationalization of the institution can be designed creatively and independently. Achievement-based independent curriculum as a manifestation of educational autonomy. This research focuses on the design and model of achievement-based independent curriculum development. The aim is to find an achievement-based independent curriculum design and model in boarding schools. This research uses a qualitative approach with the type of case study research. The results of the study found that the curriculum development design at SMA al Hikmah Boarding School was based on the competency standards of shalih, muslih, and optimal academic graduates. Meanwhile, the development step consists of four components, including philosophical construction, strengthening the foundation based on vision-mission-objectives, designing innovation programs, and producing program innovation outputs. Meanwhile, the Al Hikmah Boarding School curriculum model is independent-intergartive. The model by integrating the program into graduate competency standards is in the form of a life proposal and leadership character.